The Allocative Efficiency Analysis in the Rice Farming Production - Muslim Salam; Rafiqah Maulidiyah; Achmad Amiruddin; Pipi Diansari; Ahmad Imam Muslim (Department of Agribusiness, Faculty of Agriculture, Universitas Trunojoyo Madura, Indonesi, 2022)
The study aimed to analyze the effect of the application of production inputs on rice farming production and to analyze the allocative efficiency. The study was conducted in Bantaeng Regency. The primary data employed were collected from 36 farmers who owned 82 rice fields in total. The FPCD Model and AE Analysis were applied for the data analysis. The model showed that there were five variables (land area, seeds, ZA fertilizer, NPK fertilizer, and labor) had positive and significant effects on the rice farming production. Meanwhile, the result of EA Analysis showed that the variable of land area, seeds, and ZA fertilizer had not been efficient yet and the labor was not efficient. In increasing the rice farming production, the farmers are encouraged to cultivate more rice fields, apply for more certified seeds, ZA and NPK fertilizers, as well as reduce the number of labors used for production’s efficiency.